Street network and land use in the slum of Chouf Lekdad in Sétif (Algeria) - Alikhodja, Mehdi (Technium Social Sciences Journal, 2022)
The phenomenon of slums in Algeria dates back to the 1930s following the deterioration of the rural economy and the mass exodus to the big cities. After independence, this phenomenon was accentuated and generalized to several towns. State efforts to eradicate informal settlements and relocate their inhabitants have not succeeded in solving this problem; on the contrary, slums have evolved into permanent settlements. The Chouf Lekdad district in Sétif illustrates this evolution and this change in status, hence the need to take a different look at this type of district. The objective of this work is to explore the spatial configuration of the Chouf Lekdad district through the study of its network of streets and the distribution of houses in space. To achieve this, we opted for the theory of space syntax using the axial map, all-line analysis and the Visibility graph analysis (VGA). The results revealed a hierarchy of streets and spaces as well as the importance, of certain areas such as mechanical access and the center of the slum.